Variable within variable - Simultaneous stability and change. The case of syllable-final s in Ciudad Real - Kapović, Marko (Borealis – An International Journal of Hispanic Linguistics, 2017)
Spanish syllable-final s has been found to be completely stable in the great majority of the varieties in which it has been studied as a sociolinguistic variable. The same is true for the variety of Ciudad Real, Spain, where our data have shown not only lack of indication of any type of change at the present moment through inferences made from apparent time, but also evidence of its stability in the last hundred years by looking at the data from the available linguistic atlases. However, in our investigation, we performed a study of all the separate contexts in which the syllable-final s occurs, and it was discovered that in one of them, the sequence /s/+/t/, a different kind of behavior was registered. Namely, in this specific context, apparent-time inferences additionally supported by the older linguistic atlas data show a clear pattern of a change from above towards a normative realization of the sibilant. In this paper, we will try to explain how it is possible for a stable variable to contain within itself a subvariable which in turn shows signs of a change in progress.